Review: Privacy Preserving and Sensitive Data Hiding Methods - Tomar, Sonu; Singh, Piyush (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2015)
Privacy preserving data mining deals with hiding an individual’s sensitive identity without sacrificing the usability of data. It has become a very important area of concern but still this branch of research is in its infancy .People today have become well aware of the privacy intrusions of their sensitive data and are very reluctant to share their information. The major area of concern is that non-sensitive data even may deliver sensitive information, including personal information, facts or patterns. Several techniques of privacy preserving data mining have been proposed in literature.